IT solutions in transport management of liquid fuels. Case study of Grupa Lotos - Witkowski, Jarosław; Weremij, Tomasz (Zielona Góra: Faculty of Economics and Management Press)
The aim of the article is to present innovative IT solution for monitoring transport in the process of fuel distribution, which was implemented in Grupa Lotos in January 2013. Hardware and software requirements of the system as well as the functional and task-oriented structure were described in the article. In contrast with other standard applications supporting the management of liquid fuel supply chain it is a unique solution, which considerably contributes to a significant reduction of the levels of losses and extraordinarily increases the safety and quality of delivered goods. It is a tool which may become an important source of competitive edge during stagnation in the market of fuels.
Keywords: logistyka dystrybucji; technologie IT; rynek paliw płynnych; distribution logistics; IT technologies; liquid fuels market